2017
DOI: 10.1149/2.0021705jss
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pad Surface Micro-Texture on Tribological, Thermal and Kinetic Characterizations during Copper Chemical Mechanical Planarization

Abstract: This study investigated the effect of different pad surface micro-textures on the tribological, thermal and kinetic attributes during copper chemical mechanical planarization (CMP). Different micro-textures were generated by two different chemical vapor deposited (CVD) diamond-coated conditioner discs (i.e. Disc A and Disc B). Results showed that while pad temperature and removal rate increased with polishing pressure and sliding velocity on both discs, Disc B generated consistently lower removal rates and coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 18 publications
1
47
0
Order By: Relevance
“…The values of contact density and percentage contact area are in agreement with prior results reported by our research group. (5)(6)(7)(8)(9)(10) The values for mean summit height and mean summit curvature are similar for both magnitudes of downforce, but the values of contact density and percentage contact area are twice as large for the pad broken-in at the higher downforce. This further indicates that given enough break-in time, mean summit height and curvature will reach the same stable value, while contact density and percentage contact area will not.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The values of contact density and percentage contact area are in agreement with prior results reported by our research group. (5)(6)(7)(8)(9)(10) The values for mean summit height and mean summit curvature are similar for both magnitudes of downforce, but the values of contact density and percentage contact area are twice as large for the pad broken-in at the higher downforce. This further indicates that given enough break-in time, mean summit height and curvature will reach the same stable value, while contact density and percentage contact area will not.…”
Section: Resultsmentioning
confidence: 98%
“…The right-hand tail of the PDF curve represents the uppermost surface of the pad, shown in orange and red in the topographic images, which can also be thought of as the summits of the pad asperities. (10) This is therefore important because the summits of the pad asperities are the highest parts of the pad surface and are most likely to come into contact with the wafer during polishing. (2,3) The conditioning disc cuts the higher pad features as the pad break-in progresses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a quantitative assessment of the microscale contact state is necessary to study the material removal mechanism in CMP [2]. Some scholars have developed parametric analyses and even statistical models for microscale contact states [3]. Kim et al [4] found that increasing the pore density increased the contact rate and thus reduced the number of scratches.…”
Section: Introductionmentioning
confidence: 99%
“…hard/soft) and pad composition/properties largely impacts the CMP performance, which has been attributed to the pad asperity contact and the different slurry transport profiles as many studies have investigated the effects of pad conditioning/surface roughness, flow rate, and the coefficient of friction. 9,10,[27][28][29][30][31][32][33] While there has been some indication that the pad type correlates to the chemical interactions at the Cu/slurry/pad interface, it is necessary to further examine and validate the effects of chemical entrapment within pad asperities as they relate to corrosion inhibition modes. Better understanding the mechanism of Cu surface passivation from a dual perspective (i.e.…”
mentioning
confidence: 99%